Genetic diversity of introduced Manila clam Ruditapes philippinarum populations inferred by 16S rDNA - Chiesa, Stefania
Manila clam Ruditapes philippinarum - synonym Venerupis philippinarum (Adams and Reeve, 1850) - is one of the most successful marine invaders, being introduced worldwide for aquaculture and fisheries. Genetic diversity and structure of its populations are largely unknown, especially in the invaded environments. Herein we present molecular genetic data on 12 introduced Manila clam populations in Italy, Spain, and Portugal from both Mediterranean (Adriatic) and Atlantic sampling sites. The phylogenetic information was investigated by the direct sequencing of 16S mitochondrial DNA. Results of mtDNA analyses showed the occurrence of 11 haplotypes for European introduced populations, as a consequence of multiple founder effects from different source populations. Rp hap1 was the most frequent, shared among all populations. The other 10 haplotypes were rare and distributed at local scale, in agreement with what was observed in other invasive bivalves. Biogeographic and phylogenetic analyses based on 16S rDNA of introduced Manila clam populations showed a complex scenario, dominated by multiple pools of individuals coming from different sources, as a consequence of multiple introductions.